(untitled) (Bangladesh Journal of Animal Science, 2022)
The experiment was carried out in the south-west region of Bangladesh to understand the general goat husbandry practices and the socioeconomic significance of goat farmers. Through a face-to-face interview with these rural farmers, information was collected from a total of 100 goat farmers at random in five Upazila in the Kustia district. The majority of the farmers were illiterate and middle-class, and their main source of income was agriculture. In this region, 14% of farmers involved in goat rearing mostly raised Black Bengal goats (84%) and crossbred goats (9%). Both buck and doe were reared by 67% of the farmers. Most of the farmers (92%) practiced a semi-intensive rearing system. Among the farmers, 88% did not use bamboo or wooden platform inside houses. The farmers fed their goats green grass, green grass with straw and green grass with concentrates at 70%, 11%, and 19%, respectively. Only Napier Pakchong (43%) and German (22%) fodders were cultivated whereas 92% of farmers practiced no methods. On rainy days, the goats were nourished mostly on tree leaves and 93% of farmers did not practice their goats a winter bath. Most of the goats in the study areas were affected by pneumonia (59%) and PPR (24%) with pneumonia having a high mortality rate (28%). A good portion (87.67%) of farmers practiced vaccination against PPR. The burial method for disposal of carcasses was followed by 96% of farmers. Most of the farmers (92%) gave the anthelmintic drug to deworm their goats. These results suggested that proper training is essential for better rearing and management of goats. Bangladesh Journal of Animal Science, 51 (4): 138-144